The Exploring Health Sciences Students Reflections on Emergency Response Learning - Antoni, Marcel; Suparto, Suparto; Willian, William; Hermawan, Stepanus Maman (Journal of Language and Health, 2025)
Sudden cardiac arrest is a crita Sudden cardiac arrest is a critical medical condition requiring immediate intervention and basic emergency competencies among future healthcare professionals. Learning experiences related to emergency response are essential for health sciences students as they prepare for clinical responsibilities. This study explores students' reflections on their experiences in learning emergency response interventions, emphasizing perceived challenges and expectations for improved learning processes. A descriptive qualitative design was adopted, and data were collected through in-depth interviews with 12 health sciences students who had recently completed a formal emergency response learning module. Thematic analysis revealed four key areas: difficulty in maintaining correct procedural techniques, limited familiarity with emergency devices, performance anxiety under simulated pressure, and insufficient opportunities for repetition and feedback. Students expressed the need for extended practice time, realistic scenario-based learning, and formative assessments to reinforce competence and confidence. These reflections offer valuable insights for educators to develop more responsive, participatory, and psychologically supportive approaches in emergency response education, ultimately enhancing students' preparedness for real-life clinical challenges. ical medical condition requiring immediate intervention and basic emergency competencies among future healthcare professionals. Learning experiences related to emergency response are essential for health sciences students as they prepare for clinical responsibilities. This study explores students' reflections on their experiences in learning emergency response interventions, emphasizing perceived challenges and expectations for improved learning processes. A descriptive qualitative design was adopted, and data were collected through in-depth interviews with 12 health sciences students who had recently completed a formal emergency response learning module. Thematic analysis revealed four key areas: difficulty in maintaining correct procedural techniques, limited familiarity with emergency devices, performance anxiety under simulated pressure, and insufficient opportunities for repetition and feedback. Students expressed the need for extended practice time, realistic scenario-based learning, and formative assessments to reinforce competence and confidence. These reflections offer valuable insights for educators to develop more responsive, participatory, and psychologically supportive approaches in emergency response education, ultimately enhancing students' preparedness for real-life clinical challenges. Keywords: Education, Emergencies, Learning, Readiness, Reflection